(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The purpose of this article is to determine and assess Life Cycle Costs of biogas and fertilizer produced in anaerobic digestion of biomass. General Cost Breakdown Structure for anaerobic digestion plant is described for better understanding of the system. Main cost categories discussed in this study are: Investments; Design, construction and dismantling costs; Maintenance, Operation and Transportation costs. Results showed that Design, construction and dismantling costs have the biggest share in Total Life Cycle Cost (TLCC) per cubic meter of biogas. This category also has the biggest influence on TLCC of fertilizer. Investment costs are the second most significant cost category.